Compatibility of polyvinyl alcohol and poly(methyl vinyl ether- co-maleic acid) blends estimated by molecular dynamics - Moolman, F.S.; Meunier, M.; Labuschagne, P.W.; Truter, P.-A. (Polymer (Guilford), 2005)
The CSIR has developed a novel oxygen barrier technology for plastics packaging based on interpolymer complex formation between PVOH (polyvinyl alcohol) and PMVE-MA (poly(methyl vinyl ether- co-maleic acid)). As interpolymer complexation interactions are strongly dependent on stoichiometric ratios, the estimation of the optimum blend ratio is an important component of blend design. This study used molecular dynamics modelling to predict the ratio of optimum interaction for PVOH:PMVE-MA blends. Amorphous cells were constructed containing blends of short-chain repeat units of PVOH and PMVE-MA. The oligomers were equilibrated using both NVT and NPT dynamics and the cohesive energy densities (CED's) of the models were computed. From the CED's, energies of mixing and Flory–Huggins Chi Parameter ( χ) values were estimated. The χ-values were negative for all blends, indicating favorable interaction between the two polymers. The minimum χ-values were found around 0.6–0.7 mass fraction of PMVE-MA, which agrees well with experimental viscosity results (this work), which indicated optimum interaction around 0.7 mass fraction PMVE-MA. These results confirm that molecular dynamics can be used as a tool for investigating interpolymer complexation phenomena.